Antimicrobial Activity Of Constituents Identified In Essential Oils From Mentha And Cinnamomum Through GC-MS - NEERJA GUPTA,; GOLDY SAXENA, (International Journal of Pharma and Bio Sciences, 2010)
GS/MS of essential oils from Cinnamomum camphorum and Mentha piperita revealed the main chemical components, bornyl acetate, terpinen-4-ol, 1,8 cineole, camphor, eugenol, limonene, Î¬-pinene, β pinene, geraniol, cinnamaldehyde, linalool, borneol and menthol.GC-MS studies of the essential oils of Mentha piperita and Cinnamomum camphorum have revealed the major constituents as menthol and camphor respectively as per the retention time (area 30.07% ,mol.wt. 156.26 for menthol and 67.66% area, mol.wt.142 for camphor). Two terpenoids were subjected for the study of their antimicrobial activity against E.coli and S.aureus. Menthol showed greater zone of inhibition in 24 hrs. at maximum 2% concentration , while less zone of inhibition in 24 hrs. was observed at 2% concentration with camphor.Structure – activity relationship has been observed in the following trend. Methoxy terpene > Alcoholic Terpene > Ketonic terpene On the basis of the above observation these terpenes can be used as natural medicines in the treatment of several diseases like cold & Flu, infectious diseases, bronchitis and also as flavouring liquors, cosmetics, fragrances etc.